The impact of income adjustments in the Casen Survey on the measurement of inequality in Chile - Bravo, David; Valderrama Torres, José A. (Estudios de Economía, 2016)
The adjustment of the information obtained from household surveys to make the figures compatible with National Accounts is a non-standard and potentially questionable practice given that it alters the structure of income distribution. This paper analyzes the sensitivity of inequality and poverty indicators to the adjustments made by ECLAC so as to enable a consistency between what is reported by the CASEN survey and the National Accounts figures in Chile. The results reveal that this leads to important changes in the top-end of the distribution and to an overestimation in the main inequality indicators in Chile. Chile looks more unequal in international relative terms due to this adjustment.